Interactions between MAOA gene polymorphism and maternal parenting in predicting externalizing and internalizing problems and social competence among Chinese children: Testing the genetic vulnerability and differential susceptibility models. Issue 6 (15th February 2017) - Liu, Yapeng; Chen, Xinyin; Zhao, Siman; Way, Niobe; Yoshikawa, Hirokazu; Zhang, Guangzhen; Liang, Zongbao; Zhang, Minghao; Ke, Xiaoyan; Lu, Zuhong; Deng, Huihua
Abstract: The present study aimed to test whether monoamine oxidase A ( MAOA ) gene polymorphism was a marker of the genetic vulnerability model or the differential susceptibility model by investigating the interaction of MAOA gene polymorphism with maternal parenting on externalizing and internalizing problems and social competence among Chinese children. Participants were 290 children and their parents in China. MAOA genotypes were ascertained by polymerase chain reaction amplification. Mothers reported their parenting stress and engagement in parent–child activities when the child was 6 months old. Children's behavioral problems and social competence were rated by mothers and fathers at 48 months old. The results showed that MAOA genotypes interacted with maternal parenting stress in predicting boys' internalizing problems. Also, MAOA genotypes interacted with maternal engagement in parent–child activities in predicting boys' social competence. The analyses of regions of significance and the proportion of interaction index indicated that boys with the low‐activity genotype were at risk for (a) high internalizing problems under high maternal parenting stress and (b) low social competence if mothers displayed a low level of maternal engagement. No significant interaction effects were found among girls. The results suggested that the MAOA gene might be a marker of the genetic vulnerability model among Chinese boys. Highlights: We evaluated whether MAOA gene was a marker of the genetic vulnerability model or the differential susceptibility model by investigating the interaction of MAOA gene polymorphism with maternal parenting on behavioral problems and social competence among 4‐year‐old Chinese children. The results of regions of significance and the proportion of interaction index indicated that boys with the low‐activity genotype were at risk of high internalizing problems or low social competence with high maternal parenting stress or low engagement. No significant interaction effects were found among girls. The results indicated that MAOA gene might be a marker of the genetic vulnerability model rather than the differential susceptibility model.